Collective excitation of Bose–Einstein condensate of 23Na via high-partial wave Feshbach resonance - Zhenlian Shi; Ziliang Li; Pengjun Wang; Wei Han; Lianghui Huang; Zengming Meng; Liangchao Chen; Jing Zhang (New Journal of Physics, 2023)
We experimentally observe the collective excitation (called surface-mode excitation) of Bose–Einstein condensate of ^23 Na by ramping the external magnetic field across the high-partial wave magnetic Feshbach resonance corresponding to vary the atomic interaction. We check the collective surface mode excitation of $|1, 1\rangle$ state for the three d-wave and three g-wave Feshbach resonances below 600 G and find that only two d-wave resonances present the strong excitation, another d-wave resonance only creates a weak excitation, and all g-wave resonances do not, which reflects the strength of these magnetic Feshbach resonances. For the collective excitation, the excitation of surface modes along the axial weak-confinement and radial strong-confinement of optical dipole trap shows different characteristics. We also study the lifetime of the collective oscillation by measuring the damping rate of the oscillation amplitude, which is caused by the mechanisms of dephasing effect and collisional relaxation. This excitation method gives us a new tool for investigating the properties of ultracold quantum gases without changing the trap frequencies.